(untitled) (Semiárida, 2020)
The present study was carried out in order to evaluate forage DM accumulation of annual white sweet clover (Melilotus alba Medikus). Evaluation started when plants reached 16.5 cm in height (vegetative stage) and continued until the fructification atage. Eight treatments (sampling dates) were arrangad in a randomized complete block experimental design with three replications. Total removal of forage was done at each sampling date. Plant height, phonological Stata, forage yield, and stem:leaf:flower ratio were estimated. Mathematical models representing the relationships between the independent variable "number of days from first cut" and the dependent variables "dry matter (DM) production" and "Ieaf %" were developed. In each case the correspondent R2 was calculated. White sweetclover had a typical spring growth. The highest cumulative DM yield was observed at fructification stage (17,000 kg DM/ha). Leaf % decreased throughout the growing season from 73.4 % (July 2) to 3.4 % (January 1). Growth rate (kg DM/ha/day) was not correlated with rainfall or average temperature. Cumulative DM yield had a positive correlation with plant height, average temperature and cumulative rainfall.